An Intersection of Racism and Sexism in Toni Morrison’s Sula - Thapa, Samrakshika (International Research Journal of MMC, 2021)
This study analyzes female friendship in Sula and also focuses on the impact of race, class and gender on women’s relationships. The novel emphasizes how women face the challenges of patriarchal institutions and other attempts to subjugate through polygamy, constraints of tradition, caste prejudice and political instability. Thus, the chief aim of this study is to show how the black women are treated unfairly and suffer from male domination within their community also. The study portrays the healing powers of female bonding, which allows women to overcome prejudice and survival, to enjoy female empowerment, selfhood establishment and to extend female friendship into female solidarity that participates in nation building. However, another conclusion focuses on the patriarchy which constitutes a threat to female bonding and usually causes women’s estrangement.